The Effect Of Compensation On Organizational Commitment In Employes Of BPJS Employment Office Of East Nusa Tenggara - Benu, Yessi; Seran, Maria Claudia (Journal of Practical Management Studies, 2025)
The purpose of this study was to find out whether there is an influence on Compensation on Organizational Commitment in employees of the East Nusa Tenggara Branch of the Employment BPJS. The research method used in this research is quantitative. The number of population respondents was 35 people who were determined using non-probability sampling techniques. The data collection technique used is using observation, interviews and questionnaires this research uses simple linear regression analysis techniques. Based on the results of simple linear regression, it is known that there is a positive and significant effect of compensation on organizational commitment in employees of the East Nusa Tenggara Branch of the Employment BPJS. This is evidenced by the result that the significant level is 0.706 <0.05, so the regression mode can be used to predict the compensation variable or in other words there is a significant influence between the compensation variable (X) on organizational commitment (Y). the results of hypothesis testing state that the t-count value is 9.140> than the t-table value of 2.03, it can be said that Ho is accepted and Ha is rejected. In the sense that there is a significant effect on compensation on organizational commitment in employees of the East Nusa Tenggara Branch of the Employment BPJS.